Exploratory factor analysis of the Just Culture Assessment Tool for nursing education. (March 2021) - Walker, Danielle; Hromadik, Lora; Altmiller, Gerry; Barkell, Nina; Toothaker, Rebecca; Powell, Kevin
Background: Just culture has been identified as a vital component of safety culture by national and international organisations. In a just culture, emphasis is not placed on blaming individuals for errors but rather on examining personal and system processes that can best support safety and prevent reoccurrence. Although those in the practice arena have worked to implement the concepts of just culture, the same is not true in nursing education, leaving nursing students lacking the pre-requisite knowledge, skills and attitudes to implement just culture in practice on graduation. Aims: Assessment of this phenomena is the essential first step to align nursing education with practice in promoting just culture as a mechanism for patient safety. The purpose of this paper is to further refine the Just Culture Assessment Tool-Nursing Education through exploratory factor analysis. Methods: The Just Culture Assessment Tool-Nursing Education was adapted from the Just Culture Assessment Tool, an instrument created for the practice setting. Validity and reliability were established for the Just Culture Assessment Tool-Nursing Education in a study of 800 nursing students to assess their perceptions and understanding of just culture with their nursing programmes. Using the previously conducted data, an exploratory factor analysis was conducted. Results: Factor analysis supports six subscales, similar to that of the Just Culture Assessment Tool. However, individual items were loaded into different subscales. All subscales demonstrated good reliability. Factor analysis supported further refinement of two items to improve the instrument's ability to capture data. Conclusions: Perceptions of just culture differ between experienced providers and nursing students; nursing students have less experience with reporting errors. Factor analysis of Just Culture Assessment Tool-Nursing Education items demonstrated these differences, supporting modification of items by the instrument developers. An 'if' statement for students to consider their possible actions rather than experience was added to two items to better capture data from nursing students when completing the assessment.